Teenage Pregnancy in Nigeria from 1970 to 2023: Burden, Issues and Prospects - T, Okara Amarachi; A, Nwaodu Mercy; J, Mba Obinna; G, Osuafor Nkeiruka; S, Eze Amarachi; Eustace, Egere; U, Eze Daniel; I, Nduka Jovita; N, Ezenekwe Lizette; U, Anetoh Maureen; B, Umeh Ifeoma; A, Adenola Ugochi; et al. (Global Journal of Medical and Clinical Case Reports, 2025)
Background: Teenage pregnancy represents a multifaceted challenge that affects not only the health of adolescent girls but also the socio-economic development of communities and the nation as a whole. Objective: We narratively reviewed how socio-cultural, economic, and health system factors have influenced teenage pregnancy rates in Nigeria over time and identified opportunities for improvement. Methods: The study was a narrative review of published studies. A total number of 85 articles were obtained: 30 from PubMed, 37 from Google Scholar, and 18 from African Journals Online (AJOL). The articles were then screened for duplication and eligibility. Data was summarized with descriptive statistics. Data was summarized with descriptive statistics of frequency and percentage. Results: The studies carried out nationally were 14 (46.7%) followed by that of the southwest geopolitical zone of Nigeria 9 (30.0%). Cross-sectional studies were the most utilized study type 15 (50.0%). The majority of the studies were carried out between 2011 and 2020, 19 (63.33%). Conclusion: While the incidence and prevalence have shown some regional improvements, particularly in urban areas, the burden remains high in rural regions where socio-cultural practices such as early marriage persist. The associated health risks, including maternal and infant mortality, and the socio-economic challenges of disrupted education and poverty, highlight the urgent need for comprehensive interventions.